Turning the New Ground: Critical and Pedagogical Reflections on the Production of the First Japanese–Lithuanian Dictionary - Švambaryt, Dalia (Acta Orientalia Vilnensia, 2005)
Centre of Oriental Studies, Vilnius University This paper is based on author’s own experience of compiling the first Japanese–Lithuanian character dictionary (in Japan there are converse Lithuanian–Japanese dictionaries). It contains hermeneutical, pedagogical and pragmatic reflections on the production of bilingual dictionaries, and discusses the problem of how to make Japanese studies attractive in a country with no tradition of the studies. To create the basis for the studies, not only an intellectual background, but also linguistic material, such as textbooks, dictionaries, etc. is needed. In the case of a country where Japan has just recently become an object of academic studies, such reference book for language learning could also become the primary source of information on the country in which the language is spoken.